Association between oral hygiene and oral health-related quality of life of pregnant women (Research, Society and Development, 2020)
Objectives: The aim of this study was to assess the association between oral hygiene habits and oral health-related quality of life (OHRQoL) of pregnant women. Methodology: This cross-sectional study was conducted with a randomized sample of 100 pregnant women in a municipality in southern Brazil. OHRQoL was assessed using the Oral Health Impact Profile (OHIP-14) questionnaire. Demographic, socioeconomic and behavioral factors were collected through a structured interview. Clinical variables were obtained through examinations (gingivitis, periodontitis and dental caries). The association between predictor variables and OHIP-14 scores was evaluated using Poisson Regression models. Results are presented as Rate Ratio (RR) and a 95% confidence interval (95% CI). Results: The mean age of the sample was 24 years. The average total OHIP-14 scores were 11.54 [standard deviation (SD) 8.68]. Non-white pregnant women reported a worse OHRQoL compared with white women (RR 1.37; 95% CI 1.22-1.55). In addition, tooth brushing frequency > 2 times a day was a protective factor against negative impacts on OHRQoL compared with tooth brushing of ≤ 2 times a day (RR 0.80; 95% CI 0.70-0.92). Conclusions: Non-white women had greater impacts on OHRQoL. In addition, pregnant women who brushed their teeth >2 times a day had better OHRQoL. These findings are useful in planning strategies for improving health conditions as well as the OHRQoL of pregnant women.